EFFECTIVENESS OF PLAYING ROLE IN SOCIAL DEVELOPMENT CHILDREN IN PRESCHOOL - Indriani Yauri; Herman J Warouw; Fredrik Toluon (Jurnal Ilmiah Perawat Manado (Juiperdo), 2018)
Background: Social development is a process of learning to adjust to group norms, morals and traditions, to merge into one entity and to communicate and work together. A toddler who experiences delays in social personal development can have unfavorable effects on a child's self-concept, causing problems with his behavior and emotions. Several studies have shown that role playing can improve the social development of preschoolers. Aims : To evaluate the effects of role playing on social development in preschoolers in kindergarten. Joint Work to Build Matanga Village. Method: The research design used was Quasi Experiment with a type of pre-test and post-test control time design group with 30 respondents. Previously, this study carried out initial data collection (pre-test) to determine the level of social development of children. Furthermore, after treatment is given, the final data is collected (post-test). The sampling technique is done by simple random sampling with research instruments using observation sheets of child development tasks in the form of a checklist. Results: Data were analyzed using the Wilcoxon test to determine significant differences before and after being treated in the experimental and control groups, with the results obtained p value = 0.001 (<0.05). Conclusion: Playing an effective role on social development in preschool children. Role playing is not only done by teaching staff but can also be done by health workers to improve the social development of preschoolers.